(untitled) (Research, Society and Development, 2021)
Objective: To analyze the evidence available in the literature on the use of auricular acupuncture to reduce pain in the elderly. Methodology: Integrative literature review performed in MEDLINE, LILACS, Web of Science, Scopus, ScienceDirect and CINAHL databases, using the descriptors “elderly” (aged), “auricular acupuncture” (auricular acupuncture OR ear acupuncture) and “pain reduction” (pain). The initial search found 179 studies, original articles were included, available in full, in any language, and no time frame was adopted. After reviewing titles and abstracts, 15 remained for full text analysis. Finally, 11 studies were included in the review. Results: The effectiveness of auricular acupuncture in pain control and treatment was evidenced in different populations, such as oncologic elderly, individuals undergoing surgical procedures and with some type of pain. Conclusion: Despite the limited number of studies with the elderly, the diverse populations and the different intervention protocols, it is recommended that AA associated or not with other treatments can contribute to pain reduction in the elderly.